The Influence of Supervision and Organizational Culture on Employee Work Productivity through Organizational Commitment to Kimshafi Alung Cipta Ltd - Rezeki, Fitri; Librianty, Nany; Farhas, Rizqon Jamil (Politeknik APP Jakarta, 2023)
The purpose of this study is to examine the impact of supervisory characteristics and organizational culture on employee work productivity via organizational commitment as a mediator. This study utilized SEM because SEM may simultaneously quantify components and impacts between variables in an entire model. Utilizing the Quota Sampling method, 276 employees are sampled. Path analysis using the Structural Equation Modeling-Partial Least Square (SEMPLS) approach and the SmartPLS 3.3.3 software is used to analyze the data. The findings of this study indicate that: (1) there is a positive and significant influence of supervision variables on the Work Productivity of Kimshafi Alung Cipta Ltd; (2) there is a positive and significant influence of organizational culture variables on the Work Productivity of Kimshafi Alung Cipta Ltd; (3) there is a positive and significant influence of organizational commitment variables on the Work Productivity of Kimshafi Alung Cipta Ltd; and (4) there is a positive and significant